Analisis Pengendalian Persediaan Menggunakan Metode EOQ untuk Optimalisasi Persediaan Bahan Baku Penolong (Studi Kasus: PT. Petrokimia Gresik) - Iwan Sukarno; Mohamad Reynaldo Haykal Arshal (Program Studi Teknik Industri Universitas Setia Budi, 2023)
The availability of auxiliary materials is one of the important elements in the production process. Running out of these materials causes the product not to meet the product standards. Therefore, it is necessary to control the supply of auxiliary materials. PT. Petrokimia Gresik, in the process of making fertilizer, used auxiliary materials including Bentonite, Brucite, Red Clay, and Na/K-CO3. In this study, a comparison was made between the min-max method and Economic Order Quantity (EOQ) method. The data collected for this study include data on the use of auxiliary materials in 2021, holding costs, ordering costs, Consumption Rate (CR), lead time (LT), safety factor (SF), and unit cost. The results obtained that the use of the EOQ method can reduce the frequency of ordering auxiliary materials and provide savings in total inventory costs of up to 3% compared to the current min-max method. In addition, based on the calculation provide information that Brucite should be put on priority because it provides the highest total inventory cost compared to other auxiliary materials.